DIABETAGONIK AGENT STREPTOZOCIN TO MAKE WHITE RATS MALE DIABETES MELLITUS - Saputra, Nengah Tegar; Suartha, I Nyoman; Dharmayudha, Anak Agung Gde Oka (Buletin Veteriner Udayana, 2018)
Trend of metabolic diseases like diabetes mellitus were growth up, with morbility and mortality rate are higher. Most of research about diabetes mellitus are used to rat. Experimental diabetagonic agent was use like aloksan and streptozocin (STZ). The side effect of STZ are less than aloksan. The purpose of this study was to see the response of white rats (Rattus norvegicus) male against streptozotocin agent to make the rats in the experimental conditions of diabetes mellitus. Injection of streptozotocin agent carried by intra peritoneal with dose of 45 mg/kg. White rats have sarver before induction STZ. Level of blood glucose are measure before induction STZ (day 0) and third day after induction STZ.  The number of rats is 88 individuals. The results showed that rats provide a response to the increase in blood glucose as an indication of experimental diabetes mellitus which is indicated by a percentage value. White rats experiencing hyperglycemia as much as 54,8 % with the details of 21.5 % mild, 11.8 % moderate and 21.5 % by weight . These results indicate that a very precise Streptozotocin agent used to make experimental animals in the experimental conditions of diabetes mellitus.